ANALISIS KEBUTUHAN ENERGI LISTRIK SISTEM BALI 2013-2017 DENGAN APLIKASI SIMPLE E - Pancane, I Wayan Dikse; Suriana, I Wayan; Yasa, I Wayan Sugara (Jurnal Ilmiah Telsinas, 2019)
Electric energy cannot be kept in big scale hence this energy must always available at the time of required. As a result arises problem in facing requirement of erratic electricity from time to time, how operating an electric power system the always can fulfill request of energy power in each the time, with good grade. If energy power sent from generator far bigger than requests of energy power at payload, hence will arise problem of dissipation of energy at electrical company. While if energy power awakened sent and to be lower or doesn't fulfill requirement of consumer payload hence there will be local extinction at payload, as a result harms the side of consumer. Therefore is required adaptation between evocations with energy power request. Conditio sine qua non that is firstly must be conducted for reachs the purpose is the side of electrical company knows payload or request of electricity is future. In consequence short term payload forecast, middle and length is important task in planning and operation of power system. Intention of the research is to forecasting of payload system Bali in 5 next year causing is got requirement forecast number of electric power appropriate, with method that is simple.